CHALLENGES FACED BY HEALTHCARE INTERVENTIONS IN THE FAMILY HEALTH STRATEGY ACCORDING TO HEATHCARE PROFESSIONALS - Giordano Pedro de Oliveira; Aida Maris Peres; Maria Marta Nolasco Chaves; Elizabete Araújo Eduardo (Universidade Federal do Paraná, 2011)
This study aimed to identify easy and difficult issues noted by Family Health Strategy healthcare professionals, concerning the confrontation of family health problems and establishing how that relates to the curriculums of the degree courses. This descriptive research with a qualitative approach was carried out with the collaboration of twelve healthcare professionals from three Family Health units, between April and May 2008, who answered questions about how they provided healthcare in daily practice. The results indicated that, firstly, the graduate is not prepared to confront the contradictions of reality which impose themselves on the professional routine and that, secondly, graduates need consistent theoretical grounding to support the work processes of the Family Health Strategy. It was concluded that professional training should be based in theories which, together with more concrete familiarity with the conditions of life of the population, should permit them to carry out critical reflection and understand reality in its different dimensions and contradictions, so as to offer transformative interventions.